2022
DOI: 10.1186/s13023-022-02288-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic characterization of a cohort of 97 CLN6 patients tested at a single center

Abstract: Background Ceroid lipofuscinoses neuronal 6 (CLN6) disease belongs to the neuronal ceroid lipofuscinoses (NCLs), complex and genetically heterogeneous disorders with wide geographical and phenotypic variation. The first clinical signs usually appear between 18 months and 8 years, but examples of later-onset have also been reported. Common manifestations include ataxia, seizures, vision impairment, and developmental regression. Because these are shared by other neurological diseases, identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
4
11
0
Order By: Relevance
“…We evaluated each subjects’ previous neuroimaging to and found WMSAs were present on each subjects’ brain MRI, whether those neuroimaging studies were performed early or late in their disease course (Fig 1). WMSAs were predominantly present in the periventricular and occipital regions and were similar to previous case reports (Biswas et al, 2020; Cannelli et al, 2009; Guerreiro et al, 2013; Jadav et al, 2014; Katz et al, 2020; Rus et al, 2022; Sawiak et al, 2015; Sun et al, 2018; White et al, 2018). Brief summaries of each subject’s genotype, phenotype and white matter findings are presented in the Supplementary Information.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…We evaluated each subjects’ previous neuroimaging to and found WMSAs were present on each subjects’ brain MRI, whether those neuroimaging studies were performed early or late in their disease course (Fig 1). WMSAs were predominantly present in the periventricular and occipital regions and were similar to previous case reports (Biswas et al, 2020; Cannelli et al, 2009; Guerreiro et al, 2013; Jadav et al, 2014; Katz et al, 2020; Rus et al, 2022; Sawiak et al, 2015; Sun et al, 2018; White et al, 2018). Brief summaries of each subject’s genotype, phenotype and white matter findings are presented in the Supplementary Information.…”
Section: Resultssupporting
confidence: 90%
“…Currently, no effective therapeutic interventions have been developed for CLN6A. The CLN6A subtype typically presents with delayed language development, cognitive regression, and motor decline (Canafoglia et al, 2015;Rus et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In CLN6 mouse model brains, expression of Zip7 in PCs was altered, being shown to be higher than in control brains. Seizures are a typical symptom of CLN6 disease ( Canafoglia et al, 2015 ; Berkovic et al, 2019 ), especially in the adult form ( Rus et al, 2022 ), in which patchy loss of PCs has been observed ( Robertson et al, 2008 ). However, in the abovementioned mouse model, only PC involvement in motor symptoms was evaluated; the possible involvement of these cells in epileptic status in this model thus needs to be further evaluated.…”
Section: Neuronal Ceroid Lipofuscinosis and Purkinje Cellsmentioning
confidence: 99%